2017
DOI: 10.1016/j.cryogenics.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

ABS 3D printed solutions for cryogenic applications

Abstract: 3D printing has become a common, inexpensive and rapid prototyping technique, enabling the ad hoc fabrication of complex shapes. In this paper, we demonstrate that 3D printed objects in ABS can be used at cryogenic temperatures, offering flexible solutions in different fields. Firstly, a thermo-mechanical characterization of ABS 3D printed specimens at 77 K is reported, which allowed us to delimit the type of cryogenic uses where 3D printed pieces may be implemented. Secondly, we present three different exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The pedestal was printed with a MakerBot ® 3-D printer (Replicator2, New York, NY) using polylactic acid (PLA) thermoplastic filament (MakerBot ® Industries, LLC One MetroTech Center, 21st Fl, Brooklyn, NY 11201 USA). The PLA filament was fed through the printer head, heated to a molten state (200°C)and extruded to harden in 0.2-mm layers on a modeling plate (Bartolomé et al 2017). Our design criteria were: 1) a raised pedestal for support; 2) proper positioning for quick alignment on the device; 3) rapid classification of samples; 4) straightforward but relevant classification categories, and 5) the ability to provide standardization among user groups.…”
Section: Methodsmentioning
confidence: 99%
“…The pedestal was printed with a MakerBot ® 3-D printer (Replicator2, New York, NY) using polylactic acid (PLA) thermoplastic filament (MakerBot ® Industries, LLC One MetroTech Center, 21st Fl, Brooklyn, NY 11201 USA). The PLA filament was fed through the printer head, heated to a molten state (200°C)and extruded to harden in 0.2-mm layers on a modeling plate (Bartolomé et al 2017). Our design criteria were: 1) a raised pedestal for support; 2) proper positioning for quick alignment on the device; 3) rapid classification of samples; 4) straightforward but relevant classification categories, and 5) the ability to provide standardization among user groups.…”
Section: Methodsmentioning
confidence: 99%
“…28,29 This combination of materials gives ABS excellent toughness, even in cold conditions, such as cryogenic applications. 30 It also provides good rigidity, good thermal stability, and high resistance to chemicals and cracking due to environmental stress. ABS is inexpensive, flexible, lightweight, and easily extruded, which makes it perfect for 3D printing.…”
Section: A Abs Materials Properties and Fdm Printing Strategymentioning
confidence: 99%
“…In the category of thermoplastics, one of the most used materials is acrylonitrile butadiene styrene (ABS). 1 3 The ABS is having properties of fast solidification, average strength and cheap in price but have inferior mechanical properties. 4 8 The studies have reported the use of ABS printed parts on fused deposition modelling (FDM) in medical/surgical applications, 9 –11 anatomies models of animals and humans, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies outlined the use of nano- or micro-sized particulate for reduce/reuse/recycle (3R’s concept of waste management) prospective by FDM. 2,37 But hitherto very little has been reported on the recycling of thermosetting waste by using it as filler in thermoplastic matrix along with ceramic particulates. The present study is an extension of work reported by Singh et al 37 in which the study was limited to the preparation of innovative feedstock filaments of thermosetting, thermoplastic and ceramics blends.…”
Section: Introductionmentioning
confidence: 99%